2004
DOI: 10.1111/j.1472-765x.2004.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Escherichia coli originating from livestock faeces deposited directly onto pasture

Abstract: Aims: To determine the fate of Escherichia coli deposited onto grassland via faeces, from naturally colonized cattle, sheep or pigs. Methods and Results: Groups of cattle, sheep and pigs were penned outdoors on grass during November, and removed after 14 days. Escherichia coli populations in the ground declined over 134 days from initial average levels of 5AE34, 4AE31 and 4AE96 log 10 CFU g)1 in cattle, sheep and pig pens, respectively. The maximum Escherichia coli survival time was up to 162 days (190 days ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 13 publications
(41 reference statements)
5
88
2
Order By: Relevance
“…The controls or pure pumice samples showed little growth by any culturing method tested as expected but soils with some vegetation and bird droppings revealed also low cell counts apart from aerobic bacteria growing at 30 • C. It is noteworthy that despite high vegetation and seagull activity, we measured low numbers of faecal coliforms except in one sample (SR-17) and a few other samples with bird droppings but none of the samples contained any of the pathogens that were tested for. This suggests that the coliforms and faecal coliforms cannot survive long in the soil (Avery et al, 2004;Sun et al, 2006).…”
Section: Surface Soil Samplesmentioning
confidence: 99%
“…The controls or pure pumice samples showed little growth by any culturing method tested as expected but soils with some vegetation and bird droppings revealed also low cell counts apart from aerobic bacteria growing at 30 • C. It is noteworthy that despite high vegetation and seagull activity, we measured low numbers of faecal coliforms except in one sample (SR-17) and a few other samples with bird droppings but none of the samples contained any of the pathogens that were tested for. This suggests that the coliforms and faecal coliforms cannot survive long in the soil (Avery et al, 2004;Sun et al, 2006).…”
Section: Surface Soil Samplesmentioning
confidence: 99%
“…It has been found that E. coli O157 can survive on surface vegetation for 6 weeks but persisted when injected subsurface (77). VTEC may then be transported over land or below the surface flow to surface and ground waters.…”
Section: Survival Of Vtec In Animal Wastementioning
confidence: 99%
“…For instance, some agents can persist in soil for many months after exiting an animal's gastrointestinal tract [51,52]. The impact of animals at pasture can vary according to animal density.…”
Section: Agricultural Activitiesmentioning
confidence: 99%